2001
DOI: 10.1116/1.1405513
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic ellipsometry measurements of chromium nitride coatings

Abstract: Articles you may be interested inStructure and optical properties of pulsed sputter deposited Cr x O y ∕ Cr ∕ Cr 2 O 3 solar selective coatings

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
10
0
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 15 publications
5
10
0
3
Order By: Relevance
“…6(b). The refractive indices of the films lies in the range of 2.44 to 2.62 at 550 nm and is close to the reported values for Cr 2 N [4,19]. The film grown at 100°C has a refractive index (n) of 2.62 at 550 nm, which remains higher than those of samples deposited at 200 and 300°C for the whole range of wavelength.…”
Section: Ellipsometry Analysissupporting
confidence: 78%
“…6(b). The refractive indices of the films lies in the range of 2.44 to 2.62 at 550 nm and is close to the reported values for Cr 2 N [4,19]. The film grown at 100°C has a refractive index (n) of 2.62 at 550 nm, which remains higher than those of samples deposited at 200 and 300°C for the whole range of wavelength.…”
Section: Ellipsometry Analysissupporting
confidence: 78%
“…• (2θ) was observed that may possibly be assigned to the CrN (200) orientation [21,25]. Both phases are according to the literature thermodynamically stable [21].…”
Section: Bulk and Surface Characteristics Of Nonexposed Powdersmentioning
confidence: 86%
“…Both phases are according to the literature thermodynamically stable [21]. The main diffraction peaks of chromium metal were in addition observed.…”
Section: Bulk and Surface Characteristics Of Nonexposed Powdersmentioning
confidence: 91%
See 2 more Smart Citations